Validity and reproducibility of a food frequency questionnaire to assess dietary intake of women living in Mexico City - HERNÁNDEZ-AVILA MAURICIO; ROMIEU ISABELLE; PARRA SOCORRO; HERNÁNDEZ-AVILA JUAN; MADRIGAL HERLINDA; WILLETT WALTER (Instituto Nacional de Salud Pública, 1998)
Objective. To assess the reproducibility and validity of a 116 item semi-quantitative food frequency questionnaire (FFQ), designed to assess the relation between dietary intake and chronic diseases. Material and methods. To test the reproducibility of the FFQ questionnaire, the FFQ was administered twice to 134 women residing in Mexico City at an interval of approximately one year; to assess the validity we compared results obtained by the FFQs with those obtained by four 4-day 24-hour recalls at three month intervals. Validity and reproducibility were evaluated using regression analysis and Pearson and intraclass correlation coefficients of log-e and calorie-adjusted nutrient scores. Results. Mean values for intake of most nutrients assessed by the two food frequency questionnaires were similar. However, means for the 24-hr recall were significantly lower. Intraclass correlation coefficients for nutrient intakes, assessed by questionnaires, administered one year apart, ranged from 0.38 for cholesterol to 0.54 for crude fiber. Correlation coefficients between energy-adjusted nutrient intakes, measured by diet recalls, and the first FFQ ranged from 0.12 for polyunsaturated fatty acids to 0.67 for saturated fatty acids. Regression coefficients between 24-hr recall and FFQ,s were all significant were significant for all nutrients, except for polyunsaturated fat, folic acid, vitamin E and Zinc. Conclusions. These data indicate that this semi-quantitative FFQ is reproducible and provides a useful estimate by which to categorize individuals by level of past nutrient intake. However, its application outside Mexico City or in different age and gender populations will require additional modifications and validation efforts.